2005
DOI: 10.2144/05386su06
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Tissue™: Proteomic Profiling of Formalin-Fixed Tissues

Abstract: Identification and quantitation of candidate biomarker proteins in large numbers of individual tissues is required to validate specific proteins, or panels of proteins, for clinical use as diagnostic, prognostic, toxicological, or therapeutic markers. Mass spectrometry (MS) provides an exciting analytical methodology for this purpose. Liquid Tissue MS protein preparation allows researchers to utilize the vast, already existing, collections of formalin-fixed paraffin-embedded (FFPE) tissues for the procurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 15 publications
0
112
0
Order By: Relevance
“…Although further study is needed for mass spectral protein profiling and actual protein identifications using NDME extracts, a recent publication indicates that destructively extracted solutions from FFPE tissues can be used for proteomic investigation on a variety of mass spectrometry platforms. 19 Different applications may require different extraction conditions, requiring variation of the extraction buffer composition, or variation of the duration and/or intensity of the microwave or ultrasound treatments. Variation of these parameters may allow selective macromolecular release.…”
Section: Discussionmentioning
confidence: 99%
“…Although further study is needed for mass spectral protein profiling and actual protein identifications using NDME extracts, a recent publication indicates that destructively extracted solutions from FFPE tissues can be used for proteomic investigation on a variety of mass spectrometry platforms. 19 Different applications may require different extraction conditions, requiring variation of the extraction buffer composition, or variation of the duration and/or intensity of the microwave or ultrasound treatments. Variation of these parameters may allow selective macromolecular release.…”
Section: Discussionmentioning
confidence: 99%
“…[3] demonstrated that the proteins can be extracted from ethanol-fixed and paraffin-embedded tissue, and resolved by 2-DE separation. Recently Shi et al [4] obtained a satisfying overlapping between proteins identified from FFPE and frozen tissues and encouraging results are reported also by Prieto et al [5] and Crockett et al [6] that identified proteins from FFPE enzymatically digested tissues. However, few studies have been pursuing MALDI-TOF imaging MS (MALDI-IMS), the most challenging proteomics analysis application on FFPE section.…”
Section: Introductionmentioning
confidence: 74%
“…In order to study the different types of tissues, several methods are devoted to specific area sampling and depend on the desired size, such as macrodissection (Azimzadeh et al, 2010;Nazarian et al, 2008) or the more accurate needle microdissection (Craven et al;Prieto et al, 2005). Finally, the most precise technique to select a specific cell group in a tissue section is LCM.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…50% trifluoroethanol (TFE) for lung tissue processing was also tested (Tian et al, 2009). Commercial solutions exist for FFPE tissue processing such as the acid-deteriorating detergent RapiGest (Nirmalan et al, 2011), Liquid Tissue MS protein Prep kit (Nakatani et al, 2012;Prieto et al, 2005), Qproteome FFPE tissue kit (Becker et al, 2007), NDME-U (Chu et al, 2005), and FFPE Protein Extraction Solution (Agilent Technologies, Santa Clara, CA). Moreover, all these treatments methods can be applied with a digestion step done on Microcon (Millipore, Billerica, MA) or Vivacon (Vivaproducts, Littleton, USA) units.…”
Section: Optimal Tissue Solubilization Towards Protein Extractionmentioning
confidence: 99%